The effect of water and citric acid on sago starch bio-plastics - Ahmad, Zuraida; Yusof, Yusliza; Anuar, Hazleen; Razali, Muhammad Khairul Muhaimin (2011)
Starch is a biodegradable polymer produced in abundance from many renewable resources. In this research, bio-plastic starch (BPS) was produced from melt processing of Malaysian sago starch with the additions of glycerol as plasticizer and water as well as citric acid (CA) as a secondary additive. The main objective was to investigate the influence of CA and water contents with presence of glycerol on the mechanical properties of BPS. The CA content varies from 0 to 40 w/wt% while water was also varied from 0 to 40 w/wt%. The materials were prepared by melt blending in the Haake Rheomix at 130°C, followed by injection molding process. The properties of BPS with different CA and water content, are investigated through Fourier transform infrared (FT-IR) and tensile testing. FT-IR spectroscopy proved that acid citric improve the properties of BPS and water give negative effects to the carbon hydrogen-bond. The samples were also tested by scanning electron microscopy (SEM). It is obvious that the addition of the CA at 30 wt/wt% improve the mechanical property of BPS to more than 40% compare to the addition of water.